1995
DOI: 10.1007/bf00223911
|View full text |Cite
|
Sign up to set email alerts
|

fw 2.2:a major QTL controlling fruit weight is common to both red- and green-fruited tomato species

Abstract: We have shown that a major QTL for fruit weight (fw2.2) maps to the same position on chromosome 2 in the green-fruited wild tomato species, Lycopersicon pennellii and in the red-fruited wild tomato species, L. pimpinellifolium. An introgression line F2 derived from L. esculentum (tomato) x L. pennellii and a backcross 1 (BC1) population derived from L. esculentum x L. pimpinellifolium both place fw2.2 near TG91 and TG167 on chromosome 2 of the tomato highdensity linkage map. fw2.2 accounts for 30% and 47% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 26 publications
0
60
0
3
Order By: Relevance
“…For example, Chen and Tanksley (2004) identified 123 recombinants from 1,535 F2 individuals within the S. pennellii IL 2-5 region for the fine-mapping of se2.1 on chromosome 2. Recombination suppression varies across Solanaceae genomes and chromosomal locations (Alpert et al, 1995;Ku et al, 1999;Monforte and Tanksley, 2000;Gorguet et al, 2008), and in some regions, recombination hotspots have been identified, including on S. pennellii chromosome 9 (Fridman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen and Tanksley (2004) identified 123 recombinants from 1,535 F2 individuals within the S. pennellii IL 2-5 region for the fine-mapping of se2.1 on chromosome 2. Recombination suppression varies across Solanaceae genomes and chromosomal locations (Alpert et al, 1995;Ku et al, 1999;Monforte and Tanksley, 2000;Gorguet et al, 2008), and in some regions, recombination hotspots have been identified, including on S. pennellii chromosome 9 (Fridman et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…TA1589, from tomato (Lycopersicon esculentum), is a nearly isogenic line homozygous for the small-fruit allele from Lycopersicon pennellii, LA716, at the endogenous fw2.2 locus (Alpert et al, 1995); TA1616 is homozygous for the large-fruit allele at the endogenous fw2.2 locus and homozygous for the small-fruit allele, also from L. pennellii, introduced into an unlinked site through transgenesis (Frary et al, 2000). A series of stocks carrying zero, one, two, three, or four copies of the small-fruit alleles were selected from the progeny of a cross between TA1589 and TA1616.…”
Section: Plant Materials Growth Conditions and Genotyping Assaysmentioning
confidence: 99%
“…The map positions of the two QTL identified in this study were also found to be associated with FW in several previous studies (reviewed in Grandillo et al 1999;Chen et al 1999). Of these, fw2.2 has been reported to be conserved among the wild tomato species and is considered to be a major fruit weight QTL (Alpert et al 1995). fw2.2 was recently isolated via mapbased cloning .…”
Section: Fruit Weight (Fw)mentioning
confidence: 99%